Measuring and improving the performance of customs valuation controls: An illustration with Gabon. (10th January 2019) - Cariolle, Joël; Chalendard, Cyril; Geourjon, Anne‐Marie; Laporte, Bertrand
Abstract: Modern customs administrations aim to both facilitate legal trade and combat fraud. To meet this dual objective, many customs administrations in developing countries must give risk management a highly prominent role. In this context of modernisation, this paper first provides stylised facts on the performance of the customs controls carried out at the Gabon border. Then, we compare Gabon′s granular import customs data with international trade statistics. Based on this comparison, we identify undetected fraud and present a methodology to target ex post audits. Finally, we define indicators to monitor the performance of customs valuation controls.